The Effect of Trade Credit, Technology Investment, Competition on Firm Performance of Construction Companies in Indonesia - Wildan, Wildan; Usman, Bahtiar; Nalurita, Febria (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to analyze the impact of trade credit, technology investment, and competition on firm performance in Indonesia's construction sector, which is one of the main pillars of the national economy. Indonesia's construction industry has experienced significant growth in recent decades, but also faces complex challenges, especially post-pandemic. This study uses a quantitative approach with data from construction companies in Indonesia over the period 2019-2023. The analytical method used includes multiple linear regression to examine the relationship between the independent variables (trade credit, technology investment, and competition) and the dependent variable (firm performance). The results show that trade credit has a significant positive influence on firm performance, providing important financial flexibility in running operations. In addition, technology investment is proven to increase efficiency and innovation, which has a positive impact on performance. Competition in the industry also encourages firms to adapt and improve performance, although it can create significant pressure. The findings are expected to provide insights for companies, investors, and managers regarding effective strategies to improve firm performance in the face of challenges in the construction sector. This study also recommends the need for policies that support technology investment and sound trade credit practices to promote sustainable growth in the Indonesian construction industry.